2017
DOI: 10.1177/0033294116688892
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels and Well-Being in Older Adults

Abstract: The objective of this study was to identify the interconnectedness of different intensity levels of physical activity and psychological (life satisfaction and positive affect) and physical (physical health) well-being. Participants were from the National Study of Midlife in the United States with assessments in 2004 and aged 25 to 74 living in the United States were included in the analyses. We conducted bivariate correlations to examine significant relationships among the study variables. In addition, after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 30 publications
4
34
1
5
Order By: Relevance
“…In addition, in order to expand this field of research more work is required to specifically review LPA in order to expand the full spectrum of activity intensities (ST, light, moderate and vigorous) for older adults. This is in line with current research in the ACCELEROMETRY PROCESSING IN OLDER ADULTS 25 field of LPA and older adults that has shown LPA to be positively associated with well-being, physical health and life satisfaction (those over 60 years); and independent of other PA and ST, LPA to reduce the risk of depressive symptoms for older adults (Bae et al, 2018;Ku et al, 2018). Furthermore, as PA research is moving towards previously mentioned non-proprietary methods more research is required into the processing of raw accelerometry data.…”
Section: Recommendations For Future Researchsupporting
confidence: 90%
“…In addition, in order to expand this field of research more work is required to specifically review LPA in order to expand the full spectrum of activity intensities (ST, light, moderate and vigorous) for older adults. This is in line with current research in the ACCELEROMETRY PROCESSING IN OLDER ADULTS 25 field of LPA and older adults that has shown LPA to be positively associated with well-being, physical health and life satisfaction (those over 60 years); and independent of other PA and ST, LPA to reduce the risk of depressive symptoms for older adults (Bae et al, 2018;Ku et al, 2018). Furthermore, as PA research is moving towards previously mentioned non-proprietary methods more research is required into the processing of raw accelerometry data.…”
Section: Recommendations For Future Researchsupporting
confidence: 90%
“…In relation to intensity, some authors have shown that improvement in functional capacity takes place both in the practice of moderate activity and in the practice of high activity [18,36]. In this regard, some studies [37] have also refuted that the practice of low physical activity is ineffective for the functional improvement of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that has been approached in scientific literature is the relationship between type of physical exercise performed by older adults (low, moderate or high) and achieving better physical health combined with life satisfaction. Thus, [18] some researchers have discovered that only moderate physical activity (3-6 METs) is only related to physical health, while high activity (>6 METs) is related to life satisfaction as well as physical health. Above this, it has been observed that physical activity is also related to an improvement in functional abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Life quality of a person is strongly related to physical activities [4]. In addition, another research says that physical activities have strong influence toward life satisfaction and is positive for life [5]. Some other researches also say that physical activities are important for children [6], physical activities are important for children with asthma [7], physical activities are important for the elderly [8].…”
Section: Introductionmentioning
confidence: 99%
“…Low level of physical activities will have an impact on physical fitness, which is related to health [11]. Previous research shows the positive effect of physical activities toward life satisfaction [12], but other findings say that physical fitness has no relation to high level of life satisfaction [13]. The elderly are very vulnerable to diseases because they are at high risk of death due to infection or other complications [14].…”
Section: Introductionmentioning
confidence: 99%